Using floristics, modern systematics and phylogenetics for disentangling biodiversity hotspots across scales: a Mediterranean case study. (2nd November 2018) - Simón-Porcar, V. I.; Escudero, M.; Navarro, L.; de Castro, A.; Lorite, J.; Molina-Venegas, R.; Arroyo, J.
Abstract: Biodiversity comprises various levels of biological organisation. Global patterns of biodiversity are well established based on species occurrence. However, functional and historical processes underlying biodiversity patterns have been only recently approached. The increasingly active field of phylogenetics has allowed the rise of phylofloristic studies to help in elucidating the historical, evolutionary causes of plant biodiversity in addition to most commonly approached ecological correlates. Here, we review recent phylogeny-based studies disentangling the role of eco-geographic and historical factors on the biodiversity patterns of the Baetic–Rifan range and exemplify the use of barcoding to explore the evolutionary assembly of woody flora in the Spanish Sierra Nevada mountain range super-hotspot. Our species-level DNA barcoding approach resulted in a phylogeny potentially improving refinement of hypotheses in comparison with previous approaches based on phylogenies at genus level, and providing insights into the woody flora of Sierra Nevada subjected to systematic discussion. We show that the roles of elevation and substrate in biodiversity distribution vary according to the biodiversity component considered and also between endemic and non-endemic flora. We aim to illustrate how modern methods can further our understanding of the mechanisms underlying the assemblage of species and, consequently, the conservation of biodiversity.